Quantifying the Benefits of New Products: The Case of the Minivan - Petrin, Amil (Journal of Political Economy, 2002)
This paper proposes a technique for obtaining more precise estimates of demand and supply curves when one is constrained to market-level data. The technique allows one to augment market share data with information relating consumer demographics to the characteristics of the products they purchase. This extra information plays the same role as consumer-level data, allowing estimated substitution patterns and (thus) welfare to directly reflect demographic-driven differences in tastes for observed characteristics. I apply the technique to the automobile market, estimating the economic effects of the introduction of the minivan. I show that models estimated without micro data yield much larger welfare numbers than the model using them, primarily because the micro data appear to free the model from a heavy dependence on the idiosyncratic logit "taste" error. I complete the welfare picture by measuring the extent of first-mover advantage and profit cannibalization both initially by the innovator and later by the imitators. My results support a story in which large improvements in consumers' standard of living arise from competition as firms cannibalize each other's profits by seeking new goods that give them some temporary market power.